2021
DOI: 10.1080/00958972.2021.1876851
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of mono-substituted N-butyl-pyridinium salts: in search of ionic liquids

Abstract: Four mono-substituted N-butylpyridinium salts, 1-butyl-4dimethylaminopyridinium chloride [b4dmapy]Cl, 1-butyl-4-methylpyridinium bromide [b4mpy]Br, 1-butyl-4-methylpyridinium hexafluorophosphate [b4mpy][PF 6 ], and 1-butyl-3-methylpyridinium hexafluorophosphate [b3mpy][PF 6 ] were synthesized and characterized using single crystal X-ray diffraction. The crystal structures were examined with the intent of identifying ion interactions leading to higher melting points of the halide salts with respect to the [PF 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In ice, linear HBs always form between different water molecules. However, in IL crystals, the HB substantially deviates from a linear geometry and induces the imidazolium cation to form a zigzag packing chain motif, where the anion localizes between these zigzag chains. , These unique HBs link the cation and anion (Figure ), forming distinct zigzag configurations in crystal ILs, including EmimPF 6 , EmimBF 4 , 1,3-dimethylimidazolium chloride, 1-butyl-3-methylimidazolium chloride (BmimCl), and 1,2,4-triazolium perfluorobutanesulfonate (TAZPfBu). Physically, the formation of zigzag chains is mainly attributable to the following reasons: (1) the coupling interactions between the HB and electrostatic interactions, where the strong electrostatic attractive forces correspond to a bent HB bond, and (2) stabilization of the entire system or minimization the total potential energy, for which HBs should form between the cation and anion to the maximum extent.…”
Section: Z-bonds In Ionic Liquidsmentioning
confidence: 99%
“…In ice, linear HBs always form between different water molecules. However, in IL crystals, the HB substantially deviates from a linear geometry and induces the imidazolium cation to form a zigzag packing chain motif, where the anion localizes between these zigzag chains. , These unique HBs link the cation and anion (Figure ), forming distinct zigzag configurations in crystal ILs, including EmimPF 6 , EmimBF 4 , 1,3-dimethylimidazolium chloride, 1-butyl-3-methylimidazolium chloride (BmimCl), and 1,2,4-triazolium perfluorobutanesulfonate (TAZPfBu). Physically, the formation of zigzag chains is mainly attributable to the following reasons: (1) the coupling interactions between the HB and electrostatic interactions, where the strong electrostatic attractive forces correspond to a bent HB bond, and (2) stabilization of the entire system or minimization the total potential energy, for which HBs should form between the cation and anion to the maximum extent.…”
Section: Z-bonds In Ionic Liquidsmentioning
confidence: 99%
“…In an IL-assisted hydrothermal synthesis, this can be brought about by the combined effect of the transition-metal ion ratio (here, the Fe 2+ /Fe 3+ ratio) and the selection of suitable ILs. Recently, a structural investigation of mono-substituted N -butyl pyridinium salts by Kelley et al reported the conservation of a distinctly non-symmetrical L-shape among butyl pyridinium cations, forming extended chains of the network that bulwark the mutual anion–anion repulsions . The anions of these ILs would dominate their interactions with solutes .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a structural investigation of mono-substituted N-butyl pyridinium salts by Kelley cations, forming extended chains of the network that bulwark the mutual anion−anion repulsions. 10 The anions of these ILs would dominate their interactions with solutes. 11 The cations with halide anions displaying greater plasticity during crystallization form a uniformly weak acidic surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations